PENGARUH CAPITAL STRUCTURE, FIRM SIZE, INTELLECTUAL CAPITAL DAN PROFITABILITY TERHADAP FIRM VALUE - Dessyla, Erica; Susanti, Merry (Jurnal Paradigma Akuntansi, 2024)
Firm value for the business community, especially investors, is a focus that needs to be considered for investment considerations. This study was conducted to examine the effect of capital structure, firm size, intellectual capital, and profitability on firm value. The sample selection technique used in this study is a non-probability sampling technique with purposive sampling method. The total sample selected was 71 manufacturing companies listed on the Indonesia Stock Exchange during the period 2017 to 2020 with a total of 284 observations. The statistical tool used in this study is the Eviews 12 SV software. The results of this study indicate that intellectual capital and profitability have a significant effect on firm value, but capital structure and firm size do not have a significant effect on firm value.